Advances in Research on Down Syndrome - Dey, Subrata (IntechOpen, 2018)
This book provides a concise yet comprehensive source of current information on Down syndrome. It focuses on exciting areas of research on chromosome editing, neurogenomics and diseases associated with Down syndrome. Research workers, scientists, medical graduates and physicians will find this book as an excellent source for consultation and references. Key features of this book are chromosome engineering in Down syndrome, mental retardation and cognitive disability, prenatal diagnosis and diseases associated with Down syndrome. Although aimed primarily for research workers on Down syndrome, we hope that the appeal of this book will extend beyond the narrow confines of academic interest and be exciting to wider audience, especially parents, relatives and health care providers who work with infants and children with Down syndrome.